One pot and stepwise synthesis of some new azo thiazolidin-4-one derivatives and their biological evaluations. - Chinar M. Burhan; Awaz J. Hussein (Zanco Journal of Pure and Applied Sciences, 2023)
(2-(2-(benzyloxy)-5-((4-(6-methylbenzo[d]thiazol-2-yl)phenyl)diazenyl)phenyl)-3- substitutedphenylthiazolidin-4-ones derivatives (4a-h) have been synthesized from the reaction of 2-(benzyloxy)-5-((4-(6-methylbenzo[d]thiazol-2-yl) phenyl)diazenyl)benzaldehyde (2) with different substituted aniline, followed by cyclization with mercaptoacetic acid via either a one-pot three-component condensation and stepwise process. The structure of synthesized compounds were elucidated by FT-IR, 1H-NMR, 13C-NMR and DEPT 13C NMR. Finally, the animicrobile activity of these compounds were evaluated by the well diffusion assay against S. aureus Gram-positive and E. coli Gram-negative bacteria.